Stability of immobilized Candida antarctica lipase B during chemo-enzymatic epoxidation of fatty acids - Törnvall, Ulrika; Orellana Coca Åkerman, Cecilia; Hatti-Kaul, Rajni; Adlercreutz, Dietlind (Enzyme and Microbial Technology, 2007)
The parameters affecting the lipase activity and operational lifetime during chemo-enzymatic epoxidation of fatty acids were investigated. Immobilized Candida antarctica lipase B (Novozym (R) 435) was incubated in the presence of various reaction components (i.e. toluene, water, H2O2, oleic acid, perpalmitic acid, and epoxystearic acid, respectively) at temperatures between 20 and 60 degrees C followed by measurement of residual enzyme activity. Epoxystearic acid was shown to slightly inactivate the enzyme at 50 degrees C, while oleic acid and perpalmitic acid did not. No deactivation of the enzyme was observed in presence of toluene/water mixture within 48 h at 20-60 degrees C. In the presence of 6-12 M hydrogen peroxide, the enzyme was rather stable at 20 degrees C, while at 60 degrees C the enzyme lost activity rapidly, with the rate of deactivation increasing with increasing hydrogen peroxide concentration. These results imply that temperature control and careful dosage of hydrogen peroxide would be essential in an industrial chemo-enzymatic process. (c) 2006 Elsevier Inc. All rights reserved.